Nuclear g-factor measurement with time-dependent recoil in vacuum in radioactive-beam geometry. (March 2015) - Kusoglu, A; Stuchbery, A E; Georgiev, G; Goasduff, A; Atanasova, L; Balabanski, D L; Bostan, M; Danchev, M; Detistov, P; Gladnishki, K; Ljungvall, J; Matea, I; et al.
Abstract: A modified version of the time-differential recoil-in-vacuum (TDRIV) method, adapted for use with radioactive beams, was applied for the first time to perform a g-factor measurement on the first-excited state in 24 Mg (Ex = 1.369 MeV, t = 1.97 ps). A high precision g-factor value was obtained using predominantly H-like ions. The results obtained demonstrate the versatility of the new approach and have the precision needed for stringent tests of shell model calculations.